Urgensi Dewan Perwakilan Rakyat Republik Indonesia sebagai Badan Legislatif dalam Berkehidupan Berbangsa dan Bernegara pada Negara Republik Indonesia - Muhammad Bintang Firdausa; Refania Varetta Sugiarto (Social Science Academic, 2026)
The urgency of the House of Representatives of the Republic of Indonesia (DPR RI) as a legislative body in the Indonesian constitutional system. Using a normative juridical approach and literature study, this study shows that the House of Representatives of the Republic of Indonesia is not just a formal representative institution, but a fundamental pillar in realizing constitutional democracy, people's sovereignty, and good governance. Through the functions of legislation, budget, and supervision, the House of Representatives plays a strategic role in maintaining the balance of power, ensuring government accountability, and translating people's aspirations into public policy. Contemporary challenges such as the degradation of public trust, the politicization of laws and regulations, and the dynamics of representation emphasize the need to strengthen the integrity, transparency, and institutional capacity of the House of Representatives. In conclusion, the existence of the House of Representatives of the Republic of Indonesia is urgent and inseparable from the survival of the nation and state that is democratic, constitutional, and just.